An Experimental Study of a Nailed Soil Slope: Effects of Surcharge Loading and Nails Characteristics - Mahmoud H. Mohamed; Mohd Ahmed; Javed Mallick; Pham V. Hoa (Applied Sciences, 2021)
The earth nailing system is a ground improvement technique used to stabilize earth slopes. The behavior of the earth nailing system is dependent on soil and nailing characteristics, such as the spacing between nails, the orientation, length, and method of installation of nails, soil properties, slope height and angle, and surcharge loading, among others. In the present study, a three-dimensional physical model was built to simulate a soil nailed slope with a model scale of 1:10 with various soil nail characteristics. The simulated models consist of Perspex strips as facing and steel bars as a reinforcing system to stabilize the soil slope. Sand beds in the model were formed, using a sand raining system. The performance of nailed soil slope models under three important nails characteristics, i.e., length, spacing and orientation, with varying surcharge loading were studied. It was observed that there is a reduction in the lateral movement of slope and footing settlements with an increase in length. It was found that the slope face horizontal pressure is non-linear with different nail characteristics. The increase in length and inclination of the soil nails decreased the vertical, horizontal stress and footing settlement, while the increase in spacing of the nails increased the vertical and horizontal stress behind the soil mass.